Return-to-School Challenges for the Post-Concussion Student - Rich Bomgardner (The Advocate, 2016)
The number of concussions in sports and recreational activities are increasing on an annual basis. Students returning to school after a concussion face many challenges which can affect their learning and school reintegration process. Difficulties in learning, decreased academic performance, and classroom readjustment issues have been reported in earlier studies. The schools and teachers ability to understand basic concussion signs and symptoms, learning and classroom challenges as well as how to implement a return to learn plan play a vital role in the student’s academic success.